Characteristics of inflammatory mediators in dental pulp inflammation and the potential for their control - Kawashima, Nobuyuki; Okiji, Takashi (Frontiers in Dental Medicine, 2024)
Dental pulp is a mesenchymal connective tissue located inside the rigid encasement of the dentin.When bacteria or bacterial products invade the dental pulp, inflammation known as pulpitis is induced in this tissue. Various mediators produced during the course of pulpitis profoundly modify the pathophysiology of the inflammation. Typical mediators include cytokines, chemokines, nitric oxide, reactive oxygen species, matrix metalloproteinases, proteases, neutrophil extracellular traps, neuropeptides, and eicosanoids. Controlling these mediators may potentially lead to the healing of pulpitis and the preservation of pulp tissue. This review discusses these mediators and further explores the possibility of controlling them.